Infection control: current status. risks, research, rules and recycling. (2nd April 2021) - Haworth, Jennifer; Sandy, Jonathan; Ireland, Anthony J
Abstract : We are living through a period of immense change following the outbreak of the COVID-19 pandemic in mainland China in December 2019. Even before the pandemic, the cost of managing healthcare-associated infections in the UK was considerable. The risk of acquiring any infection from the dental environment must be reduced to a minimum. As we have observed in recent years, new infectious agents emerge frequently, and the dental profession must be ready to respond appropriately and quickly. Orthodontic practice presents unique challenges in relation to infection control procedures. The impact of healthcare waste on the environment must also be considered. CPD/Clinical Relevance: This paper describes the range of infectious agents posing a risk to dental team members and patients. The aim is to place the recent coronavirus pandemic in the context of other recent emerging infections. Some of the latest research regarding infection control procedures is reviewed. Current best practice is described.